A Stability Indicating RP-HPLC Method Validation for simultaneous estimation of Azelnidipine and Telmisartan in a fixed-dose combination (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The present investigation deals with the validation of the developed method using RP-HPLC for simultaneous estimation of Azelnidipine as well as Telmisartan in a fixed-dose combination (FDC). The method was developed using RP-HPLC, Inertsil C-18 Column with 150×4.6 mm× 5 µm at column oven temperature 40°C, flow rate 1.5 mL/min, volume 10 µL and run time 12.0 minutes at 254 nm using Acetonitrile and buffer as mobile phase in various ratio. The developed protocol was most accurate, repeatable, and detectable towards Azelnidipine and Telmisartan in combination without any unwanted interference. When evaluated on various parameters like system suitability, precision, accuracy, linearity, robustness, force degradation study it can be concluded that the method is efficient in separating the API from its degradants and can be utilized for analyzing the samples of Azelnidipine and Telmisartan.